Optimalisasi Manajemen Guru TPQ Desa Glindah melalui Pendampingan Intensif Bersama KSPPS BMT Khoiru Ummah - Pristiwiyanto; Ach.Khusnan; Nanang Abdillah (Lembaga Pengembangan Kinerja Dosen, 2024)
Teaching the Al-Qur’an is the core of Islamic education, with the main aim of guiding children in reading, studying and understanding the Koran from an early age. The Al-Qur'an Education Park (TPQ) serves as an important platform to instill a love of the Al-Qur'an in children. Even though many TPQs have been successful with good administration and management and a large number of students, there are still TPQs that have not developed, such as the TPQ in Glidah Kedamean Village, Gresik. Observations show that learning management at TPQ does not meet recognized management and curriculum standards in education, resulting in suboptimal educational attainment. Responding to this problem, the Glidah Village TPQ Teacher Management Optimization team, together with KSPPS BMT Khoiru Ummah, initiated an intensive community service-based mentoring program using the Participatory Action Research (PAR) method. The mentoring process involves several stages, starting from identifying problems through field observations, organizing and planning programs, to implementing program actions. The results of discussions and implementation of mentoring revealed a number of problems faced by teachers regarding TPQ management. The implementation of this mentoring activity has been empirically proven to have a positive impact, increasing the effectiveness of management and the quality of education at the TPQ.